STUDENTS’ ATTITUDE TOWARDS TRANSLANGUAGING STRATEGIES IN INDONESIAN ENGLISH LANGUAGE EDUCATION CLASSROOMS - Annisa Rahmadani (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2023)
This quantitative investigation delves into the employment of translanguaging strategies within classrooms of an English education study program at an Indonesian public university. As an emerging pedagogical approach in bilingual and multilingual educational settings, translanguaging encompasses the dynamic utilization of students' linguistic repertoires to bolster learning and communication. This study seeks to explore students' attitudes towards the enactment of translanguaging during their presentation and discussion sessions and assess its potential impact on their learning experiences. A purposive sample of 50 second and third-year undergraduate students majoring in English language education study, actively engaged in translanguaging practices during presentations and discussions, was selected for this study. Data collection entailed administering a survey questionnaire comprising Likert scale items formulated to evaluate students' attitudes towards translanguaging. The gathered data were analyzed employing descriptive statistical techniques. The findings reveal that participants exhibit a favorable attitude towards the practice of translanguaging in their presentation and discussion sessions. Students reported that translanguaging amplified their comprehension of subject matter, facilitated communication with peers, and cultivated a more inclusive and diverse learning environment. The study's results suggest that integrating translanguaging strategies within English education study program classrooms can positively impact students' learning experiences and foster a constructive attitude towards linguistic diversity. Further inquiry is recommended to probe the enduring effects of translanguaging practices on students' language competence and scholastic achievements, in addition to examining potential impediments and obstacles to implementing translanguaging across various educational contexts.